Genetic Variation of Apolipoprotein E (ApoE) in Surabaya, Palu and Alor Populations of Indonesia - Pramudji Hastuti; Abdul Salam Mudzakir Sofro; Ahmad Husain Asdie; Ahmad Hamim Sadewa (Indonesian Journal of Biotechnology, 2011)
Apolipoprotein E (ApoE) has been considered to play an important role in cardiovascular disorders.Several studies reported that genetic variation in ApoE locus influence plasma lipoprotein level. The objectivesof this study was to compare the frequency of ApoE genotypes and alleles in some populations of Indonesia.One hundred and ninety five voluntarily unrelated apparently healthy individuals were recruited fromSurabaya, Palu and Alor representing the western, middle and eastern populations of Indonesia, respectively.Blood samples were collected from each subject for DNA extraction. The common allelic variants of ApoE werescreened using polymerase chain reaction (PCR) and restriction fragment length polymorphism. Three allelesi.e. ε2, ε3 and ε4 were identified and five genotypes i.e. ApoE ε2/ε2, ApoE ε2/ε3, ApoE ε3/ε3, ApoE ε2/ε4, ApoE ε3/ε4 were found in three populations studied, while ApoE ε4/ε4 was absent in Surabaya, representing the westernpopulations of Indonesia. The frequency of ε2, ε3 and ε4 alleles in the western population were 0.208, 0.701and 0.092 respectively; in the middle population were 0.242, 0.618 and 0.140 respectively and in the easternpopulation of Indonesia were 0.267, 0.466 and 0.267 respectively. The highest frequency of ε2 and ε4 allelewas found in the eastern population of Indonesia. The distribution of ε2 allele were not significantly differentamong all Indonesian populations, but significantly different were found in ε3 and ε4 allele in the easternpopulation compared to those in the western and middle populations of Indonesian. It can be concluded thatthe frequency of three ApoE alleles in the western and middle populations of Indonesia was not significantlydifferent however, significantly different was observed in the frequency of ApoE ε3 and ε4 alleles from theeastern compared to those in the western and middle populations of Indonesia.